2013
DOI: 10.4161/auto.24797
|View full text |Cite
|
Sign up to set email alerts
|

ATG4B/autophagin-1 regulates intestinal homeostasis and protects mice from experimental colitis

Abstract: The identification of inflammatory bowel disease (IBD) susceptibility genes by genome-wide association has linked this pathology to autophagy, a lysosomal degradation pathway that is crucial for cell and tissue homeostasis. Here, we describe autophagy-related 4B, cysteine peptidase/autophagin-1 (ATG4B) as an essential protein in the control of inflammatory response during experimental colitis. In this pathological condition, ATG4B protein levels increase in parallel with the induction of autophagy. Moreover, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 61 publications
4
57
0
Order By: Relevance
“…ATG4 mutations are also linked to some inflammatory bowel diseases (IBDs), as genetic variants in ATG4A and ATG4D have been proposed to contribute to granuloma formation in Crohn's disease (89). Additionally, patients with IBD show low expression of ATG4B in colon (77). These observations of altered ATG4 function in IBD are consistent with the fact that disrupted autophagy results in impaired processing of bacterial components, triggering the exacerbated inflammatory responses that characterize these disorders (90)(91)(92)(93)(94).…”
Section: Dysregulation Of Atg4 Proteases In Diseasementioning
confidence: 68%
See 1 more Smart Citation
“…ATG4 mutations are also linked to some inflammatory bowel diseases (IBDs), as genetic variants in ATG4A and ATG4D have been proposed to contribute to granuloma formation in Crohn's disease (89). Additionally, patients with IBD show low expression of ATG4B in colon (77). These observations of altered ATG4 function in IBD are consistent with the fact that disrupted autophagy results in impaired processing of bacterial components, triggering the exacerbated inflammatory responses that characterize these disorders (90)(91)(92)(93)(94).…”
Section: Dysregulation Of Atg4 Proteases In Diseasementioning
confidence: 68%
“…We have also found that mutant mice lacking ATG4B show altered secretion and assembly of otoconial components in the inner ear vestibular regions, ultimately leading to balance disorders (75,76). Moreover, Atg4b-deficient mice show impaired release of lysozyme granules in Paneth cells during dextran sodium sulfate-induced (DSS-induced) experimental colitis, resulting in exacerbated inflammation that leads to the death of these animals (77). This surprising role of ATG4B in protein secretion has also been described in bone resorption by osteoclasts (78), pointing to a novel function of autophagy in secretory cells (79) and further supporting the idea that ATG proteins are involved in non-canonical autophagic processes (80)(81)(82).…”
Section: R E V I E W S E R I E S : a U T O P H A G Ymentioning
confidence: 93%
“…36,63,64 Here, we directly demonstrated aggravated experimental colitis in myeloid cell-specific autophagy-knockout mice, leading to increased mortality. In addition, we observed apparently increased colonic tissue expression of pro-Il1b and Il6 that are important players in colitis of DSS-treated Atg7 cKO mice compared to Atg7 cWT mice, [36][37][38] while the induction of Il6 was marginal.…”
Section: Figure 7 Systemic Inflammation and Bacterial Invasion Aftermentioning
confidence: 72%
“…Notably, deletion of Atg5 in the intestinal epithelium also showed Paneth cell and granule abnormalities, while other IECs appeared to be normal [42]. Additionally, loss of Atg7 and Atg4B produces similar defects as ATG16L1 hypomorphic mice, leading to Paneth cell abnormalities, once again highlighting this cell type's sensitivity to autophagy disruption [55,56].…”
Section: Autophagy In Intestinal Inflammationmentioning
confidence: 89%